The Biological Role of PI3K Pathway in Lung Cancer - Kostas N. Syrigos; Muhammad W. Saif; Evangelos G. Sarris (MDPI AG, 2012)
Lung cancer is the primary cause of cancer-related mortality worldwide and although improvements in treatment have been achieved over the last few years, long-term survival rates for lung cancer patients remain poor. Therefore, there is an imperative need for molecularly targeted agents that will achieve long-term disease control. Numerous downstream molecular pathways, such as EGF/RAS/RAF/MEK/ERK and PI3K/AKT/mTOR are identified as having a key role in the pathogenesis of various forms of human cancer, including lung cancer. PI3K/AKT/mTOR signal pathway is an important intracellular signal transduction pathway with a significant role in cell proliferation, growth, survival, vesicle trafficking, glucose transport, and cytoskeletal organization. Aberrations in many primary and secondary messenger molecules of this pathway, including mutations and amplifications, are accounted for tumor cell proliferation, inhibition of apoptosis, angiogenesis, metastasis and resistance to chemotherapy-radiotherapy. In this review article, we investigate thoroughly the biological role of PI3K pathway in lung cancer and its contribution in the development of future therapeutic strategies.